MOSAIC THINKING IN THE CONTEXT OF THE UNIVERSITY LIBRARY ACTIVITY - Dovgan, Oleksij V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
In article describes the features of the place and role of the phenomenon clip thinking in the context of library science; analyzed taking into account the specificity of the phenomenon outlined in library practice in the background updating of libraries in modern conditions; It outlined the problem of visualization of culture as a milestone clip thinking; published proposals on the new strategy of libraries, taking into account the above-mentioned.